2021
DOI: 10.1186/s13567-020-00871-0
|View full text |Cite
|
Sign up to set email alerts
|

Protection studies of an excretory–secretory protein HcABHD against Haemonchus contortus infection

Abstract: Unlike the successful immunization of native H. contortus antigens that contributed to the realization of the first commercial vaccine Barbervax, not many studies revealed the encouraging protective efficacies of recombinant H. contortus antigens in laboratory trials or under field conditions. In our preliminary study, H. contortus α/β-hydrolase domain protein (HcABHD) was demonstrated to be an immunomodulatory excretory–secretory (ES) protein that interacts with goat T cells. We herein evaluated the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Because of the immunomodulatory features during parasite-host interaction, rHcABHD was considered a promising vaccine target. Indeed, administration of recombinant HcABHD in goats led to a moderate reduction of FECs [ 69 ]. Another ES antigen, adhesion-regulating molecule 1 (HcADRM1), was expressed in E. coli in its soluble form and tested in goats.…”
Section: Vaccination Against H Contortusmentioning
confidence: 99%
“…Because of the immunomodulatory features during parasite-host interaction, rHcABHD was considered a promising vaccine target. Indeed, administration of recombinant HcABHD in goats led to a moderate reduction of FECs [ 69 ]. Another ES antigen, adhesion-regulating molecule 1 (HcADRM1), was expressed in E. coli in its soluble form and tested in goats.…”
Section: Vaccination Against H Contortusmentioning
confidence: 99%
“…Considerable effort has also gone into identifying and evaluating immunogenic proteins present in the secretome of Haemonchus contortus [ 43 , 44 , 45 ]. Using co-immunoprecipitation, combined with shotgun LC-MS/MS, Lu et al [ 45 ] identified 114 ES proteins that interact with host T cells, including a series of proteases, SCP/TAPS proteins and C-type lectins.…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodesmentioning
confidence: 99%
“…Using co-immunoprecipitation, combined with shotgun LC-MS/MS, Lu et al [ 45 ] identified 114 ES proteins that interact with host T cells, including a series of proteases, SCP/TAPS proteins and C-type lectins. Thus, this study provided a first insight into the interplay between this parasite ( via ES products) and the immune system ( via effector cells), and also proposed possible vaccine candidates, such as the α/β-hydrolase domain protein (HcABHD), of which a recombinant version has been reported to achieve up to 70% protection against Haemonchus contortus challenge infection in a subsequent study [ 44 ].…”
Section: Recent High-throughput Proteomic Explorations Of Parasitic Nematodesmentioning
confidence: 99%
“…Bu et al demonstrated that rHcftt-2 identified from HcESPs reduced mean eggs per gram in feces (EPG) and worm burdens by 26.46 and 32.33%, respectively ( 16 ). More recently, H. contortus α/β-hydrolase domain protein (HcABHD) was identified as an immunomodulatory antigen that interacts with goat T cells, and it could induce significant reductions in egg shedding (54%) and worm burden (74.2%) ( 17 ). Given the performance of ES antigens for their immunogenicity and performance in recombinant forms, it was meaningful to explore more new ES proteins and their active form in vaccine development.…”
Section: Introductionmentioning
confidence: 99%